2015
DOI: 10.1016/j.envexpbot.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and distribution of zinc in the leaves and roots of the hyperaccumulator Noccaea caerulescens

Abstract: Highlights-Zn uptake by N. caerulescens tranlocated to leaves.-Great ability of young N. caerulescens plants to accumulate Zn in shoots.-Decrease of Ca and P concentration with increasing amount of Zn treated.-Zn crystals found in leaf epidermal cells and root cortex of N. caerulescens.-In the plant tissues, P and S co-localized while Ca localized with Zn. AbstractUnderstanding the uptake mechanisms of heavy metals by hyperaccumulators is necessary for improving phytoextraction options to reduce metal toxiciti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 30 publications
10
40
1
Order By: Relevance
“…Zn/Cd hyperaccumulator species Noccaea caerulescens (DINH et al, 2015). The C and O relative concentrations in specialized A. angustifolia needle tissues followed this descending order: adaxial epidermis> abaxial epidermis> mesophyll palisade> spongy mesophyll and, spongy mesophyll> abaxial epidermis>mesophyll palisade>adaxial epidermis, respectively (Figure 3a, b).…”
Section: Elemental Distribution In Epidemis and Mesophyllmentioning
confidence: 91%
See 1 more Smart Citation
“…Zn/Cd hyperaccumulator species Noccaea caerulescens (DINH et al, 2015). The C and O relative concentrations in specialized A. angustifolia needle tissues followed this descending order: adaxial epidermis> abaxial epidermis> mesophyll palisade> spongy mesophyll and, spongy mesophyll> abaxial epidermis>mesophyll palisade>adaxial epidermis, respectively (Figure 3a, b).…”
Section: Elemental Distribution In Epidemis and Mesophyllmentioning
confidence: 91%
“…Advanced microscopy and spectroscopy techniques have allowed for a more comprehensive assessment of the elemental composition of plant tissues (DINH et al, 2015;KRIEGER et al, 2017). In the evaluation of elemental accumulation, studies have concentrated on the elemental distribution in different tissues and plant cells (CONN; GILLIHAM, 2010) including crystals (HE et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reveal that an increasing Zn concentration may reduce the uptake of other elements such as Mn (Lombi et al, 2001;Foroughi et al, 2014) and P (Zhao et al, 1998 The preliminary results for N. caerulescens (Dinh et al, 2015) showed that Ca and Zn co-localize in the leaf tissues, but uptake of Ca was reduced up to 50% by increasing concentrations of Zn.…”
Section: Introductionmentioning
confidence: 89%
“…The seeds were then germinated on wet filter papers in the dark in a temperature-controlled glasshouse (22±3 °C) for 7 days (Dinh et al, 2015). One week-old uniform seedlings were transplanted into foam strips to keep the plants in direct contact with a basal nutrient solution made up of the following (in μM) (Monsant et al, 2010) applied to the hydroponics 12 weeks after the seedlings were transferred to the pots.…”
Section: Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation